From the Girmitiya to the Makful Sketching the continuity in migrant labour systems - Katyayani S. (My University, 2025)
This article seeks to draw parallels between two different migration systems – the Girmitiya system, also known as the Indian indentureship of the nineteenth century and the Kafala system, under which migration in the Gulf Cooperation Council (GCC) nations take place – by studying the common elements in both systems such as a binding contract, immobility and racial segregation of living quarters. Contractual arrangements of this nature in these systems typically involve agreements that commit workers for extended periods to specific locations while simultaneously imposing legal or practical limitations on their ability to terminate the contract or exercise freedom of movement. Debt relations often play a significant role in shaping these forms of labour. Indebtedness forces individuals into such contracts, while the accumulation of debt often traps them, preventing them from leaving coercive agreements. Instead, they are compelled to extend their stay by signing new contracts. Labourers are, thus, confronted with risky choices and temporary suspensions of basic human rights. The article also examines how migrants historically circumvented the Girmitiya system through everyday acts of resistance – such as indolence and absence from work – drawing on James C. Scott’s (1990) concept of ‘infra politics’. It then compares these tactics with those employed today under the Kafala regime by the Makfuls (migrants working under the Kafala), including strategies like the Khalli-Walli (free visa system), Azaad visa and care or ethnic/social networks, focusing specifically on migrants from Bihar in North India. © 2024, Shreya Katyayani.